Size-Tunable Natural Mineral-Molybdenite for Lithium-Ion Batteries Toward: Enhanced Storage Capacity and Quicken Ions Transferring - Jiang, Feng; Li, Sijie; Ge, Peng; Tang, Honghu; Khoso, Sultan A.; Zhang, Chenyang; Yang, Yue; Hou, Hongshuai; Hu, Yuehua; Sun, Wei; Ji, Xiaobo (Frontiers in Chemistry, 2018)
Restricted by the dissatisfied capacity of traditional materials, lithium-ion batteries (LIBs) still suffer from the low energy-density. The pursuing of natural electrode resources with high lithium-storage capability has triggered a plenty of activities. Through the hydro-refining process of raw molybdenite ore, containing crushing–grinding, flotation, exfoliation, and gradient centrifugation, 2D molybdenum disulfide (MoS2) with high purity is massively obtained. The effective tailoring process further induce various sizes (5, 2, 1 and 90 nm) of sheets, accompanying with the increasing of active sites and defects. Utilized as LIB anodes, size-tuning could serve crucial roles on the electrochemical properties. Among them, MoS2-1 μm delivers an initial charge capacity of 904 mAh g−1, reaching up to 1,337 mAh g−1 over 125 loops at 0.1 A g−1. Even at 5.0 A g−1, a considerable capacity of 682 mAh g−1 is remained. Detailedly analyzing kinetic origins reveals that size-controlling would bring about lowered charge transfer resistance and quicken ions diffusion. The work is anticipated to shed light on the effect of different MoS2 sheet sizes on Li-capacity ability and provides a promising strategy for the commercial-scale production of natural mineral as high-capacity anodes.